2004
DOI: 10.1021/ja049966r
|View full text |Cite
|
Sign up to set email alerts
|

A Limiting Speed for Protein Folding at Low Solvent Viscosity

Abstract: Because protein folding dynamics are heavily overdamped, Kramers theory predicts the rate of folding to scale inversely with the reaction friction, which is usually interpreted to mean the solvent viscosity. This does not mean, however, that the speed of folding can increase without limit as solvent viscosity decreases. We show that, in a sufficiently fast-folding protein, the folding speed approaches a finite limit at low solvent viscosity, indicating a reaction controlled by internal friction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
93
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 17 publications
8
93
0
Order By: Relevance
“…For simple barrier-crossing processes, D ‡ ϭ RT/ , where the friction coefficient, , is proportional to the solvent viscosity, , so a plot of vs. should be linear with zero intercept. The crucial assumption in determining the viscosity dependence is, of course, that the viscogen does not alter the free energy surface, but only changes the observed relaxation rate through its effect on the dynamics of motion on the surface, namely D ‡ .In all but one of the previous protein folding studies a chemical denaturant was used to counter the increase in stability caused by the viscogen and thereby maintain a constant equilibrium population of folded to unfolded molecules (equal to u / f ) (11)(12)(13)(15)(16)(17). The use of denaturant to maintain a constant equilibrium population ratio does not guarantee that the free energy surface, defined by the 5 parameters of Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For simple barrier-crossing processes, D ‡ ϭ RT/ , where the friction coefficient, , is proportional to the solvent viscosity, , so a plot of vs. should be linear with zero intercept. The crucial assumption in determining the viscosity dependence is, of course, that the viscogen does not alter the free energy surface, but only changes the observed relaxation rate through its effect on the dynamics of motion on the surface, namely D ‡ .In all but one of the previous protein folding studies a chemical denaturant was used to counter the increase in stability caused by the viscogen and thereby maintain a constant equilibrium population of folded to unfolded molecules (equal to u / f ) (11)(12)(13)(15)(16)(17). The use of denaturant to maintain a constant equilibrium population ratio does not guarantee that the free energy surface, defined by the 5 parameters of Eq.…”
mentioning
confidence: 99%
“…In all but one of the previous protein folding studies a chemical denaturant was used to counter the increase in stability caused by the viscogen and thereby maintain a constant equilibrium population of folded to unfolded molecules (equal to u / f ) (11)(12)(13)(15)(16)(17). The use of denaturant to maintain a constant equilibrium population ratio does not guarantee that the free energy surface, defined by the 5 parameters of Eq.…”
mentioning
confidence: 99%
“…Nevertheless, results from recent experiments on small peptides under different solvent conditions indicate that intrachain interactions (which can be interpreted kinetically as a kind of internal friction) induce local activation barriers that renormalize the effective monomer diffusion coefficient (48,49). Although controversial, internal friction may explain why the speed limit of protein folding is fixed at ϳO(0.1-1.0 s) (50).…”
Section: Resultsmentioning
confidence: 99%
“…Recently it was shown that internal friction varies substantially along the folding pathway of a peptide chain which suggests a connection between friction and formation of hydrogen bonds upon folding [66]. While such studies on proteins are ubiquitous [68][69][70], there is obviously a lack of experimental data on roughness of DNA and RNA conformational transition. …”
Section: Internal Frictionmentioning
confidence: 99%